Pengayaan Wawasan Siswa-Siswi SDIT Qurrota A’yun Dalam Budidaya Jamur Tiram Putih (Pleurotus ostreatus) Melalui Kegiatan Outing Class - Suharno; Supeni Sufaati; Irma Rahayu; Fawuni G.A.G. Rumbrawer; Annisa A. Ruhani; Irjayanti; Nancy O. Wambrauw; Wilda Z. Muhhida (Bakti Hayati: Jurnal Pengabdian Indonesia, 2025)
Oyster mushroom cultivation is an activity that can be introduced to school students as an effective learning tool. This activity introduces children to the growth process of oyster mushrooms and increases their awareness of environmental and sustainability issues. It is also an interesting teaching and learning process that motivates students to actively participate in learning through various techniques, such as an outing class. The outing class activity focused on enriching the knowledge of SDIT Qurrota A'yun students in oyster mushroom cultivation science at the greenhouse of the biology department at FMIPA UNCEN. The activity took place from February to May of 2025. Fifty fifth-grade students attended the Outing Class. The activity aimed to educate students about oyster mushrooms, teach them how to cultivate white oyster mushrooms, and inform them about the benefits of oyster mushrooms in everyday life. Methods included focus group discussions, participatory planning, and practice. The results showed that the outing class increased students' interest and enthusiasm in learning outside the school environment. Out of 100% of the total participants, approximately 67% knew about white oyster mushrooms. Questionnaires and the activity showed an increase in knowledge about identifying and cultivating oyster mushrooms. It is hoped that this activity will motivate students to participate